Analysis of Measles and Rubella Immunoglobulin G Titers in COVID-19 Patients - Başbulut E; Bilgin M; İşler H; Şen A; Kılıç SS; Çubukçu M (Dove Medical Press, 2024)
Eşe Başbulut,1 Melek Bilgin,1 Hacer Işler,1 Ahmet Şen,2 Süleyman Sırrı Kılıç,3 Mahcube Çubukçu4 1Department of Medical Microbiology, Samsun Training and Research Hospital, Samsun, Turkey; 2Department of Anesthesia and Reanimation, Trabzon Faculty of Medicine, Trabzon, Turkey; 3Department of Infectious Disease and Clinical Microbiology, Samsun Training and Research Hospital, Samsun, Turkey; 4Department of Family Medicine, Samsun University Faculty of Medicine, Samsun, TurkeyCorrespondence: Mahcube Çubukçu, Tel +905052332232, Fax +903623111522, Email mahcube.cubukcu@samsun.edu.trBackground: The objective of this study is to compare the measles immunoglobulin G (IgG) and rubella IgG levels in patient groups with mild and severe COVID-19 disease and reveal the possible relationship.Methods: This study was conducted among COVID-19-confirmed patients over 18, under 65 years of age. This study involved 75 participants- divided into two groups. The first group usually comprised asymptomatic patients who did not require hospitalization (n=43), and the second group consisted of patients who had diffuse pneumonia on thoracic CT and required hospitalization (n=32).Results: Anti-measles and anti-rubella IgG titers were detected to be higher in the group with severe disease compared to the group with mild disease (p=0.001 and p=0.001, respectively). The analyses were repeated by taking n=27 in Group 1 and n=27 in Group 2, which were similar in terms of age, gender and number. In the analysis performed without any age difference between the groups, no significant difference was found between the two groups in terms of Anti Measles IgG antibody titers (p=0.068). However, Anti Rubella antibody titers were found to be higher in the group with severe COVID-19 disease than in those with mild disease (p=0.03). Regardless of the severity of the disease, there was a positive correlation between Anti Rubella and Anti Measles IgG antibody titers and age (p=< 0.001 Spearman's rho 0.517; p=0.008 Spearman's rho 0.304, respectively).Conclusion: We believe that the pre-existing Anti-Rubella IgG antibodies in the patient may increase in parallel with the patient's viral load by recognizing the common macrodomain of SARS-CoV-2 and Rubella viruses. The common macrodomain of SARS-CoV-2 and Rubella viruses is also present in the attenuated rubella virus used in the MMR vaccine4. In this case, we predict that previously administered MMR vaccine may be protective for COVID-19 patients. disease compared to those with mild disease.Keywords: COVID-19, measles, rubella, antibody, SARS-CoV-2, immunoglobulin G